The Effects of COVID-19 on Primary School Teaching in Afrika - Rose Richardo (TOPAZART, 2023)
This study explored the consequences that the COVID-19 pandemic did to primary school teaching in a Afrika context. From February, 2020 to September, 2020, students in Afrika did not take any traditional classes at school. Instead, the government took a novel measure to move all the courses online so that the students and the teachers did not need to go to the school but they could still have their normal lessons continued. However, primary school teachers were not required to give any online lessons for children due to the children’s lack of the ability to study independently and infrastructure. The study using interviews from Human Right Watch. The main findings of the study were: 1) Students did not receive lesson. 2) Students don’t have facilitate for learning. 3) Education need cost and some parent cannot provide it. The findings also suggest that the government in Afrika should make more policies and regulations to prepare for the future.